With a little help from our pediatrician: An intervention to promote mathematics-related home activities through regular well-child visits - Tomasetto, Carlo; LeFevre, Jo-Anne; Passolunghi, Maria Chiara; De Vita, Chiara; Guardabassi, Veronica; Brunelli, Antonella; Ciotti, Francesco; Biasini, Giancarlo (Frontiers in Psychology, 2022)
Children’s involvement in mathematics-related activities in the home environment is associated with the development of their early numeracy over the preschool years. Intervention studies to promote parents’ awareness and provision of mathematics-related home activities are however scant. In this study we developed and tested the effectiveness of a non-intensive intervention program delivered by community pediatricians to promote mathematics-related activities in the home environment. Parents of 204 Italian children were invited to report on the frequency of mathematics-related home activities when children attended to the first (3 years, 8 months of age on average) and to the third preschool year (5 years, 6 months of age on average). At both waves, children were also assessed on their early numeracy. In occasion of the routine well-child visit at age 5, parents randomly allocated to the intervention condition (vs. a business-as-usual control condition) received guidance on age-appropriate home mathematics-related practices to sustain children’s numerical development. Results revealed that parents in the intervention group improved their provision of home mathematics-related activities at the post-intervention assessment (relative to baseline) to a greater extent than parents in the control condition. No effect was observed on children’s early numeracy. Overall, results are promising in suggesting that community pediatricians may be a resource to promote home mathematics-related activities though non-intensive low-cost interventions.